6G vision requirements and technology trend prospect - Kejun WEI; Po HU (Dianxin kexue)
As 5G enter the critical phase of commercial deployment,some countries launched research of the next-generation mobile communication technologies (6G).The development trends of information communication technology was analysed firstly,on this basis,the 6G vision and main features of 6G were discussed,and then the potential technology trends of 6G was analysed,in order to provide direction suggestions for the subsequent 6G research.